Without You, I'm Nothing: Performances of the Self on Twitter. - PAPACHARISSI, ZIZI (International Journal of Communication (19328036), 2012)
Online social platforms collapse or converge public and private boundaries, creating both opportunities and challenges for pursuing publicity, privacy, and sociality. Presentations of the self thus become networked performances that must convey polysemic content to audiences, actual and imagined, without compromising one's own sense of self. This study explored how individuals perform the self through the use of Twitter trending hashtags. Content and discourse analyses were used to examine performative strategies and the form of performance in 140 or fewer characters. Findings underscored play as a dominant performative strategy and pointed to the reordering of grammar, syntax, and literary conventions as prevalent ways through which play is performed. Affect, redaction, and deliberative improvisation frame performances that become part of the ongoing storytelling project of the self on Twitter.